Occupational Sex Composition and Gendered Housework Performance: Compensation or Conventionality?. Issue 2 (13th December 2016) - McClintock, Elizabeth Aura
Abstract: This article examines the association between occupational sex composition and housework, considering total housework time, time on male‐typed and female‐typed tasks, and the percent of total time spent on male and female tasks. Previous research examining male‐ and female‐typed chores independent of total housework suggests that couples compensate for gender‐atypical employment through gender‐typical housework performance, but this analysis of the National Survey of Families and Households (1992–1994) and the American Time Use Survey (2003–2013) demonstrates that assuming a quadratic association and failing to contextualize gendered housework performance within total housework performance obscures the true relationship between occupation and housework. In fact, women and men in gender‐atypical occupations perform a more gender‐atypical combination of chores. The influence of gender deviance neutralization in the housework literature may overshadow alternative explanations and model specifications. In particular, by assuming a quadratic association, researchers may impose, rather than test, gender deviance neutralization.